Strategi Komunikasi Pemasaran Honda Big Bike Astra Motor Semarang Dalam Meningkatkan Jumlah Penjualan - Nurfindra Triembong Heningadi; Hapsari Dwiningtyas Sulistyani (Interaksi Online, 2021)
This research with the title Marketing Communication Strategy of Honda Big Bike Astra Motor Semarang in Increasing Total Sales. This research is focused on the Marketing Communication Strategy that has been implemented at PT. Astra Motor Semarang in the Honda Big Bike division. The results of data collection and interviews found that the sales data of the Honda Big Bike had significant differences in the ups and downs of sales achievements in 2016, 2017 and 2018. In 2016, sales of the Honda Big Bike were 7 units, then increased sharply in 2017, namely 32 units, then sales fell again in 2018 to only 19 units. The first factor that affects the achievement of motorcycle sales in 2017 is the intense promotion in the form of media advertisements, personal selling and holding a promotional cast which is carried out every month in 2017. The second factor is sufficient ready stock of Honda motorbikes, so that the waiting period for orders (indent purchase) is not too long because consumers of this type of big bike generally want cash purchases. The third factor is that the price per unit is still affordable for people in Semarang and Central Java. In 2018 there was an unexpected decrease in sales achievement, namely to only 19 units, from the information data obtained by researchers due to the reduced frequency of exhibition event promotions compared to 2017. The motorbike's “ready stock” supply was reduced due to restrictions on imported goods regulations, resulting in consumers who will buy in cash cancels the purchase plan. The enthusiasm of some people, especially in big cities, for the lifestyle of riding motor sports and large motorbikes, the sale of large motorbikes still has a great opportunity. The results showed that the Honda Big Bike Division PT. Astra Motor Semarang has used the Promotion mix theory which has 4 elements of a promotional strategy, namely Advertising, Sales Promotion, Publicity, Personal Selling, which aims to increase sales volume, in addition to product introduction, as well as attracting customers and instilling a good image of the company. Of all the strategies that have been implemented, Personal selling is one of the most dominant promotional strategies, appropriate and effective for selling speciality goods such as the Honda Big Bike which has high value.